Literature study: Activity of white turmeric (Curcuma zedoaria) as an anti-inflammatory - Ni Nyoman Wahyu Udayani; Ni Nyoman Ayu Puspita Sari; I Made Agus Sunadi Putra; I Putu Tangkas Suwantara; Maria Malida Vernandes Sasadara; Ni Putu Lilis Adnyani (Journal of Midwifery and Nursing, 2023)
Inflammation is a response given by the body to protect the body against cellular damage, characterized by swelling, redness accompanied by a sensation of heat and pain. Long term use of NSAIDs (Non Steroid Anti Inflammatory Drugs) has side effects such as ulcers, stomach upset, bleeding, nausea, disturbances in the kidneys and the cardiovascular system. White turmeric (Curcuma zedoaria) is a plant that can be used as an anti-inflammatory. This study aims to determine the anti-inflammatory activity of White Turmeric (Curcuma zedoaria) through a literature review in the form of national and international articles or journals. The results of a study of 8 articles that met the inclusion requirements showed that White Turmeric has anti-inflammatory activity. The content of curcumin, essential oils and flavonoids in white turmeric has similarities with NSAIDs, namely by inhibiting the formation of inflammatory mediators.